Reasons for encounter in general practice: evolutionary trend in the last decade in Central Portugal - Santiago, Luiz Miguel (2022)
Objective: Analyse the reasons for encounters, classified in chapters using ICPC-2 (International Classification for Primary Care – 2) by general practitioners in the Central Region of Portugal between 2010 and 2018. Methods: Cross-sectional observational study of the reasons for encounter classified by general practitioners from three primary health centres clusters in the area of the Regional Health Centre Administration, randomly selected, in 2010, 2012, 2014, 2016, and 2018. We obtained anonymized data organized by gender, year, the total number of consultations, number of consultations with ICPC-2 classification as the reason for encounter, and the ICPC-2 chapters recorded, calculating the dynamics and growth. Results: In a total of 12.569.898 consultations performed, 5.3% were the reason for encounter classified. The ICPC-2 top-ranked chapters in all years of study were, in descending order, A (15.4%), L (11.3%), D (10.3%), R (8.4%), S (9.7%), and K (7.9%). The lowest ranked chapters in all years of study were, in increasing order, Z (1.6%), Y (1.7%), B (1.9%), W (2.1%), H (2.9%), and N (3.7%). Chapter Z recorded the highest growth dynamics from 2010 to 2018 (∆=+1.15). Discussion: In a decade of socio-economic problems, the reasons for encounters classified using ICPC-2 remained unchanged. Classifying reasons for encounter, even if it is replete with quality and volume problems can help in the quality and result of the consultation these results being like what is found in the literature. Conclusion: ICPC-2 classification of reasons for consultation by general practitioners was verified in 5.3% of consultations, and the chapters were invariable over time. Chapter Z registered the highest trends by volume of classification.